Mitral annular disjunction: A case series and review of the literature - Wu, Stephanie; Siegel, Robert J. (Frontiers in Cardiovascular Medicine, 2022)
Mitral annular disjunction (MAD) is an abnormal displacement of the mitral valve leaflet onto the left atrial wall and is commonly found in patients with mitral valve prolapse (MVP). The diagnosis is usually made by transthoracic echocardiography (TTE) although findings can be subtle and further cardiac imaging may be necessary. MAD has been associated with a risk of malignant ventricular arrhythmias and sudden cardiac death, therefore recognition of this diagnosis and risk stratification are highly important. In this review, we will discuss the diagnosis, clinical implications, risk stratification and management of MAD based upon currently available literature, as well as provide a series of cases showing the heterogeneity in presentation and our experience with management of this rare but potentially fatal entity.